Energy mix and its implications on the Vietnamese economy by 2030: A CGE analysis using GTAP-E-Power - Nguyen Duy Chinh; Ko Jong-Hwan (Economics and Business Review)
This study uses the GTAP-E-Power model to examine the economic and environmental implications of transitioning to different energy generation mixes in Vietnam by 2030. Three scenarios were considered for that year: (1) low-coal and high-gas, (2) low-coal and high-renewables, and (3) high-coal. Scenario 2 emerges as the most balanced approach, resulting in a 1.02% GDP decline and a 0.78% increase in CO2 emissions. In this scenario, the electronics sector grows slightly (+0.3%), while metals (–3.1%) and chemical products (–1.0%) experience moderate declines. In terms of exports, Scenario 2 gives rise to an increase in the trade balance (151 million USD) and a modest gain in exports to China (+0.46%), Japan (+0.37%), Korea (+0.33%), and Western Europe (+0.35%). Across all three scenarios, the output of the electronics industry shows sensitivity to energy mix changes, while the coal mining sector seems to be resilient to changing the energy mix.